Preparation method and application of manganese ion doped modified ferric sodium pyrophosphate positive electrode material
Through the preparation method of manganese ion doping modified sodium ferric pyrophosphate positive electrode material, the problem of low reversible capacity and rate performance of sodium ion batteries is solved, and higher cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202510020337.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The reversible capacity and rate performance of existing sodium ion batteries is mainly due to the inhibition of sodium ion diffusion of sodium ion by sodium ion produced during iron-based phosphate synthesis.
The preparation method of the modified sodium ferric pyrophosphate positive electrode material by manganese ion doping is reduced to reduce the local iron concentration to inhibit the formation of iron phosphate impurities, and improve the structural stability and electron conductivity of the material.
The cycle stability and rate performance of sodium ion batteries are significantly improved, and the conductivity of the material and the diffusion kinetics of sodium ions are enhanced.
Smart Images

Figure HDA0005231177910000011 
Figure HDA0005231177910000012 
Figure HDA0005231177910000021
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, belonging to the technical field of lithium ion battery positive electrodes. Background Art
[0002] Iron phosphate (Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 , NFPP) has low cost, no resource limitation, environmentally friendly, theoretical capacity (129mAhg -1 ) is good, and the volume change during the (de)sodiumization process is small (less than 4%), which can be used as the active material of the positive electrode of sodium ion batteries. However, during the synthesis of iron-based phosphate, due to improper control of reaction conditions and too long or too short reaction time, diaspore NaFePO always exists in NFPP materials. 4 Impurities, inactive sodium iron mica NaFePO 4 Due to its compact framework structure, sodium ion diffusion is inhibited, thereby reducing the reversible capacity and rate performance of NFPP materials. Summary of the invention
[0003] In view of the problems of low reversible capacity and rate performance of existing sodium ion batteries, the present invention proposes a preparation method and application of manganese ion-doped modified sodium iron pyrophosphate positive electrode material. By reducing the local iron concentration by manganese ions, the formation of iron phosphate impurities can be significantly inhibited, so that the battery has higher cycle stability and rate performance.
[0004] A method for preparing a manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, the specific steps are as follows:
[0005] (1) adding a sodium source, a phosphorus source, and a carbon source to ethanol and mixing them uniformly to form a mixed solution, adding an iron source and a manganese source to the mixed solution in sequence and mixing them uniformly to form a slurry, and then ball milling the slurry and drying it to obtain a precursor powder;
[0006] (2) The precursor powder is calcined under a protective atmosphere to obtain a manganese-doped carbon-coated sodium iron phosphate pyrophosphate material.
[0007] Preferably, the iron source in step (1) is ferric phosphate, ferric nitrate, ferric oxide, ferrous oxalate or iron powder; the carbon source is one or more of citric acid, ascorbic acid, glucose, sucrose, polyethylene glycol, and dopamine hydrochloride; the phosphorus source is ammonium dihydrogen phosphate, diammonium hydrogen phosphate or sodium dihydrogen phosphate, and the sodium source is sodium pyrophosphate, sodium acetate, sodium carbonate or sodium dihydrogen phosphate; and the manganese source is manganese acetate, manganese carbonate, manganese sulfate or manganese acetate.
[0008] Preferably, the molar ratio of the phosphorus source, sodium source, iron source and manganese source in step (1) is 4:4:3-x:x, where x=0.15-0.45; and the carbon source is 10-15% of the total mass of the phosphorus source, sodium source, iron source and manganese source.
[0009] Preferably, the ball milling speed in step (1) is 200-500 r / min, the time is 10-16 h, the ball-to-material mass ratio is 10-20:1, and the solid mass content of the slurry after ball milling is 45-50%.
[0010] Preferably, the drying method in step (1) is spray drying, air drying or vacuum drying.
[0011] More preferably, the feed rate of the spray drying is 60-90 mL / min, the feed temperature is 220°C, and the discharge temperature is 90-100°C.
[0012] Preferably, the calcination conditions of step (2) are: in a protective atmosphere, heating to a temperature of 300-350°C at a heating rate of 2-3°C / min for a first-stage constant temperature calcination for 2-3h, and then heating to a temperature of 500-550°C at a heating rate of 5-8°C / min for a second-stage constant temperature calcination for 10-12h.
[0013] Preferably, the protective atmosphere is nitrogen or an inert atmosphere.
[0014] The manganese ion doped modified sodium iron phosphate pyrophosphate positive electrode material is used as the active ingredient of the sodium ion battery positive electrode: the manganese ion doped modified sodium iron phosphate pyrophosphate positive electrode material, conductive carbon black and a binder (polyvinylidene fluoride) are evenly mixed, and then N-methylpyrrolidone is added for homogenization to obtain an active material coating; the active material coating is evenly coated on a positive electrode conductive substrate (aluminum foil), and then rolled after drying to obtain a sodium ion battery positive electrode.
[0015] The mass ratio of the manganese ion doped modified sodium iron phosphate pyrophosphate positive electrode material, conductive carbon black and binder (polyvinylidene fluoride) is 8:1:1, and the liquid-solid ratio ml:g of the added amount of N-methylpyrrolidone to the total mass of the manganese ion doped modified sodium iron phosphate pyrophosphate positive electrode material, conductive carbon black and binder (polyvinylidene fluoride) is 1 to 1.5:1.
[0016] The thickness of the active material on the conductive substrate (aluminum foil) of the positive electrode of the sodium ion battery is 10 to 20 μm.
[0017] Mechanism of improving cycle stability and rate performance of sodium ion batteries with manganese ion-doped modified sodium iron pyrophosphate as active component:
[0018] 1. Enhanced structural stability: Sodium iron pyrophosphate has a specific crystal structure. When manganese ions are doped into its crystal lattice, they can replace the position of iron ions to a certain extent because the radius of manganese ions is similar to that of iron ions. This substitution can stabilize the crystal structure and prevent structural collapse caused by the insertion and extraction of sodium ions during the charge and discharge process.
[0019] 2. Improve electronic conductivity. Doping with manganese ions can change the electronic structure of the material. Usually, pure sodium iron phosphate pyrophosphate has low electronic conductivity, which limits its reaction kinetics during battery charging and discharging. Manganese ions have different electronic configurations, and when doped into the material, new electronic conduction channels can be formed.
[0020] 3. Improve the sodium ion diffusion kinetics. In sodium ion batteries, the diffusion rate of sodium ions in the positive electrode material is crucial. Manganese ion doping can optimize the ion diffusion channels in the material. Doped manganese ions may cause slight changes in the lattice parameters of the material, thereby adjusting the diffusion path of sodium ions.
[0021] The beneficial effects of the present invention are:
[0022] The present invention reduces the local iron concentration by manganese ions, which can significantly inhibit the generation of iron phosphate impurities, reduce its band gap and ion migration energy barrier, and thus significantly improve Na + The electrical conductivity of ions and electrons gives the battery high cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD pattern of the manganese ion-doped modified sodium iron pyrophosphate positive electrode material of Example 1;
[0024] Figure 2 This is a SEM image of the manganese ion-doped modified sodium iron pyrophosphate positive electrode material of Example 1;
[0025] Figure 3 The charge and discharge curve of the sodium ion battery in Example 1 at room temperature and 0.2C current;
[0026] Figure 4 This is the cycle stability diagram of the sodium ion battery in Example 1 at room temperature and 1C current;
[0027] Figure 5 The charge and discharge curve of the sodium ion battery in Example 2 at room temperature and 0.2C current;
[0028] Figure 6 This is the cycle stability diagram of the sodium ion battery in Example 2 at room temperature and 1C current;
[0029] Figure 7The charge and discharge curve of the sodium ion battery in Example 3 at room temperature and 0.2C current;
[0030] Figure 8 This is the cycle stability diagram of the sodium ion battery in Example 3 at room temperature and 1C current;
[0031] Fig. 9 The charge and discharge curve of the sodium ion battery in Example 4 at room temperature and 0.2C current;
[0032] Fig.10 This is the cycle stability diagram of the sodium ion battery in Example 4 at room temperature and 1C current. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0034] Example 1: A method for preparing a manganese ion-doped modified sodium iron pyrophosphate positive electrode material, the specific steps are as follows:
[0035] (1) sodium dihydrogen phosphate and a carbon source (citric acid and polyethylene glycol) are added to deethanol and mixed evenly to form a mixed solution, an iron source (ferric nitrate) and a manganese source (manganese acetate) are added to the mixed solution in turn and stirred evenly to form a slurry, and the slurry is ball-milled and spray-dried to obtain a precursor powder; the molar ratio of the sodium dihydrogen phosphate, the iron source (ferric nitrate) and the manganese source (manganese acetate) is 4:2.9:0.1, and the total amount of the carbon source (citric acid and polyethylene glycol) added is 10% of the total mass of the sodium dihydrogen phosphate, the iron source (ferric nitrate) and the manganese source (manganese acetate); the ball milling speed is 200 r / min, and the time is 16 h; the ball-to-material mass ratio is 10:1, and the solid mass content of the slurry after ball milling is 45%; the feed rate of the spray drying is 60 mL / min, the feed temperature is 220° C., and the discharge temperature is 90° C.;
[0036] (2) In a nitrogen atmosphere, the precursor powder is heated to 300° C. at a heating rate of 2° C. / min for a first-stage constant temperature calcination for 2 h, and then heated to 520° C. at a heating rate of 5° C. / min for a second-stage constant temperature calcination for 10 h to obtain manganese ion-doped sodium iron phosphate;
[0037] The purity of the manganese ion-doped modified sodium iron pyrophosphate positive electrode material in this embodiment is 99.12%;
[0038] The manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, conductive carbon black and a binder (polyvinylidene fluoride) are uniformly mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone is added for homogenization to obtain an active material coating; the active material coating is uniformly coated on a positive electrode conductive substrate (aluminum foil), and then rolled after drying to obtain a sodium ion battery positive electrode; the thickness of the active material on the conductive substrate (aluminum foil) of the sodium ion battery positive electrode is 100 μm;
[0039] In a Universal (2440 / 750) inert gas glove box, a CR2032 button half-cell was assembled in the order of anode shell, sodium sheet (as anode), diaphragm (glass fiber diaphragm), electrolyte (commercial NaClO4 electrolyte), sodium ion battery cathode, gasket, shrapnel, and cathode shell. The electrochemical performance of the CR2032 button half-cell was tested using a Xinwei CT-4008 battery testing system, with a voltage test range of 1.2-4.5V.
[0040] The charge and discharge curve of the sodium ion battery of this embodiment at room temperature and 0.2C current is shown in FIG. Figure 3 ,from Figure 3 It can be seen that the sodium ion battery has a charge capacity of 115.23mAh / g, a discharge capacity of 107.21Ah / g, and an efficiency of 93.04%.
[0041] The cycle stability diagram of the sodium ion battery of this embodiment at room temperature and 1C current is shown in Figure 4 ,from Figure 4 It can be seen that the capacity retention rate of the sodium ion battery is 99.35% after 200 cycles.
[0042] Example 2: A method for preparing a manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, the specific steps are as follows:
[0043] (1) adding a phosphorus source (ammonium dihydrogen phosphate), a sodium source (sodium carbonate), and a carbon source (glucose) to deethanol and mixing them uniformly to form a mixed solution, adding an iron source (ferrous oxalate) and a manganese source (manganese carbonate) to the mixed solution in turn and stirring them uniformly to form a slurry, and the slurry is ball-milled and spray-dried to obtain a precursor powder; the molar ratio of the phosphorus source (ammonium dihydrogen phosphate), the sodium source (sodium carbonate), the iron source (ferrous oxalate), and the manganese source (manganese carbonate) is 4:4:2.7:0.3, and the total amount of the carbon source (glucose) added is 15% of the total mass of the phosphorus source (ammonium dihydrogen phosphate), the sodium source (sodium carbonate), the iron source (ferrous oxalate), and the manganese source (manganese carbonate); the ball milling speed is 300 r / min, and the time is 14 h; the ball-to-material mass ratio is 14:1, and the solid mass content of the slurry after ball milling is 48%; the feed rate of the spray drying is 70 mL / min, the feed temperature is 220° C., and the discharge temperature is 95° C.;
[0044] (2) In a nitrogen atmosphere, the precursor powder was heated to 320° C. at a heating rate of 2.5° C. / min for a first-stage constant temperature calcination for 2.2 h, and then heated to 530° C. at a heating rate of 6° C. / min for a second-stage constant temperature calcination for 10.5 h to obtain manganese ion-doped sodium iron phosphate;
[0045] The purity of the manganese ion-doped modified sodium iron pyrophosphate positive electrode material in this embodiment is 98.91%;
[0046] The high-purity sodium iron phosphate pyrophosphate positive electrode material NFPP, conductive carbon black and binder (polyvinylidene fluoride) are uniformly mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone is added for homogenization to obtain an active material coating; the active material coating is uniformly coated on a positive electrode conductive substrate (aluminum foil), and then rolled after drying to obtain a sodium ion battery positive electrode; the thickness of the active material on the conductive substrate (aluminum foil) of the sodium ion battery positive electrode is 90 μm;
[0047] In a Universal (2440 / 750) inert gas glove box, a CR2032 button half-cell was assembled in the order of anode shell, sodium sheet (as anode), diaphragm (glass fiber diaphragm), electrolyte (commercial NaClO4 electrolyte), sodium ion battery cathode, gasket, shrapnel, and cathode shell. The electrochemical performance of the CR2032 button half-cell was tested using a Xinwei CT-4008 battery testing system, with a voltage test range of 1.5-4.2V.
[0048] The charge and discharge curve of the sodium ion battery of this embodiment at room temperature and 0.2C current is shown in FIG. Figure 5 ,from Figure 5 It can be seen that the sodium ion battery has a charge capacity of 112.06 mAh / g, a discharge capacity of 105.23 mAh / g, and an efficiency of 93.90%.
[0049] The cycle stability diagram of the sodium ion battery of this embodiment at room temperature and 1C current is shown in Figure 6 ,from Figure 6 It can be seen that the capacity retention rate of the sodium ion battery after 100 cycles is 99.65%.
[0050] Example 3: A method for preparing a manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, the specific steps are as follows:
[0051] (1) adding sodium dihydrogen phosphate and a carbon source (dopamine hydrochloride) to deethanol and mixing them evenly to form a mixed solution, adding an iron source (ferric phosphate) and a manganese source (manganese phosphate) to the mixed solution in turn and stirring them evenly to form a slurry, and then ball-milling the slurry and spray-drying the slurry to obtain a precursor powder; the molar ratio of the sodium dihydrogen phosphate, the iron source (ferric phosphate), and the manganese source (manganese phosphate) is 4:2.5:0.5, and the total amount of the carbon source (dopamine hydrochloride) added is 12% of the total mass of the sodium dihydrogen phosphate, the iron source (ferric phosphate), and the manganese source (manganese phosphate); the ball milling speed is 400 r / min, and the time is 12 h; the ball-to-material mass ratio is 16:1, and the solid mass content of the slurry after ball milling is 48%; the feed rate of the spray drying is 80 mL / min, the feed temperature is 220° C., and the discharge temperature is 98° C.;
[0052] (2) In a nitrogen atmosphere, the precursor powder was heated to 350° C. at a heating rate of 3° C. / min for a first-stage constant temperature calcination for 2.8 h, and then heated to 540° C. at a heating rate of 7° C. / min for a second-stage constant temperature calcination for 11 h to obtain manganese ion-doped sodium iron phosphate;
[0053] The purity of the manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material in this embodiment is 98%;
[0054] The high-purity sodium iron phosphate pyrophosphate positive electrode material NFPP, conductive carbon black and binder (polyvinylidene fluoride) are uniformly mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone is added for homogenization to obtain an active material coating; the active material coating is uniformly coated on a positive electrode conductive substrate (aluminum foil), and then rolled after drying to obtain a sodium ion battery positive electrode; the thickness of the active material on the conductive substrate (aluminum foil) of the sodium ion battery positive electrode is 100 μm;
[0055] In a Universal (2440 / 750) inert gas glove box, a CR2032 button half-cell was assembled in the order of anode shell, sodium sheet (as anode), diaphragm (glass fiber diaphragm), electrolyte (commercial NaClO4 electrolyte), sodium ion battery cathode, gasket, shrapnel, and cathode shell. The electrochemical performance of the CR2032 button half-cell was tested using a Xinwei CT-4008 battery testing system, with a voltage test range of 1.5-4.2V.
[0056] The charge and discharge curve of the sodium ion battery of this embodiment at room temperature and 0.2C current is shown in FIG. Figure 7 ,from Figure 7 It can be seen that the sodium ion battery has a charge capacity of 85.19 mAh / g, a discharge capacity of 84.26 mAh / g, and an efficiency of 98.67%.
[0057] The cycle stability diagram of the sodium ion battery of this embodiment at room temperature and 1C current is shown in Figure 8 ,from Figure 8 It can be seen that the capacity retention rate of the sodium ion battery after 200 cycles is 98.25%.
[0058] Example 4: A method for preparing a manganese ion-doped modified sodium iron pyrophosphate positive electrode material, the specific steps are as follows:
[0059] (1) adding sodium dihydrogen phosphate and a carbon source (ascorbic acid and sucrose) to deethanol and mixing them uniformly to form a mixed solution, adding an iron source (iron oxide) and a manganese source (manganese acetate) to the mixed solution in turn and stirring them uniformly to form a slurry, and subjecting the slurry to ball milling and vacuum drying at a temperature of 120° C. to obtain a precursor powder; the molar ratio of the sodium dihydrogen phosphate, the iron source (iron oxide), and the manganese source (manganese acetate) is 4:2.85:0.15, and the total amount of the carbon source (ascorbic acid and sucrose) added is 12% of the total mass of the sodium dihydrogen phosphate, the iron source (iron oxide), and the manganese source (manganese acetate); the ball milling speed is 500 r / min, and the time is 10 h; the ball-to-material mass ratio is 20:1, and the solid mass content of the slurry after ball milling is 50%;
[0060] (2) In a helium atmosphere, the precursor powder was heated to 320° C. at a heating rate of 2.5° C. / min for a first-stage constant temperature calcination for 3 h, and then heated to 550° C. at a heating rate of 8° C. / min for a second-stage constant temperature calcination for 12 h to obtain manganese ion-doped sodium iron phosphate;
[0061] The purity of the manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material in this embodiment is 97%;
[0062] The high-purity sodium iron phosphate pyrophosphate positive electrode material NFPP, conductive carbon black and binder (polyvinylidene fluoride) are uniformly mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone is added for homogenization to obtain an active material coating; the active material coating is uniformly coated on a positive electrode conductive substrate (aluminum foil), and then rolled after drying to obtain a sodium ion battery positive electrode; the thickness of the active material on the conductive substrate (aluminum foil) of the sodium ion battery positive electrode is 95 μm;
[0063] In a Universal (2440 / 750) inert gas glove box, a CR2032 button half-cell was assembled in the order of anode shell, sodium sheet (as anode), diaphragm (glass fiber diaphragm), electrolyte (commercial NaClO4 electrolyte), sodium ion battery cathode, gasket, shrapnel, and cathode shell. The electrochemical performance of the CR2032 button half-cell was tested using a Xinwei CT-4008 battery testing system, with a voltage test range of 1.5-4.2V.
[0064] The charge and discharge curve of the sodium ion battery of this embodiment at room temperature and 0.2C current is shown in FIG. Fig. 9 ,from Fig. 9 It can be seen that the sodium ion battery has a charge capacity of 92.49 mAh / g, a discharge capacity of 91.82 mAh / g, and an efficiency of 99.27%.
[0065] The cycle stability diagram of the sodium ion battery of this embodiment at room temperature and 1C current is shown in Fig.10 ,from Fig.10 It can be seen that the capacity retention rate of the sodium ion battery after 200 cycles is 97.56%.
[0066] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The specific steps are as follows: (1) adding a sodium source, a phosphorus source, and a carbon source to ethanol and mixing them uniformly to form a mixed solution, adding an iron source and a manganese source to the mixed solution in sequence and mixing them uniformly to form a slurry, and then ball milling the slurry and drying it to obtain a precursor powder; (2) The precursor powder is calcined under a protective atmosphere to obtain a manganese-doped carbon-coated sodium iron phosphate pyrophosphate material.
2. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: In step (1), the iron source is ferric phosphate, ferric nitrate, ferric oxide, ferrous oxalate or iron powder; the carbon source is citric acid, ascorbic acid, glucose, sucrose, polyethylene glycol or dopamine hydrochloride; the phosphorus source is ammonium dihydrogen phosphate, diammonium hydrogen phosphate or sodium dihydrogen phosphate; the sodium source is sodium pyrophosphate, sodium acetate, sodium carbonate or sodium dihydrogen phosphate; the manganese source is manganese acetate, manganese carbonate, manganese sulfate or manganese acetate.
3. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the phosphorus source, sodium source, iron source and manganese source in step (1) is 4:4:3-x:x, where x=0.15-0.45; and the carbon source is 10-15% of the total mass of the phosphorus source, sodium source, iron source and manganese source.
4. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: Step (1) The ball milling speed is 200-500 r / min, and the time is 10-16 h; the ball-to-material mass ratio is 10-20:1, and the solid mass content of the slurry after ball milling is 45-50%.
5. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The drying method in step (1) is spray drying, air drying or vacuum drying.
6. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 5, characterized in that: The feed rate of the spray drying is 60-90 mL / min, the feed temperature is 220° C., and the discharge temperature is 90-100° C.
7. The method for preparing the manganese ion-doped modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The calcination conditions of step (2) are as follows: in a protective atmosphere, heating to a temperature of 300-350°C at a heating rate of 2-3°C / min for a first-stage constant temperature roasting for 2-3h, and then heating to a temperature of 500-550°C at a heating rate of 5-8°C / min for a second-stage constant temperature calcination for 10-12h.
8. Use of the manganese ion-doped modified sodium iron phosphate pyrophosphate positive electrode material prepared by the method according to any one of claims 1 to 7 in preparing a positive electrode for a sodium ion battery.
Citation Information
Cited By
Preparation method and application of sodium ion battery positive electrode material
CN120717431A
Composite modified mixed sodium ferric pyrophosphate positive electrode material and preparation method thereof
CN121355223A
Polyanion sodium ion battery positive electrode composite material
CN121376952A
A polyanionic sodium-ion battery cathode composite
CN121376952B
Porous composite electrode material and preparation method and application thereof
CN121416445A